Wide bandgap phase change material tuned visible photonics - Dong, Weiling (2020)
Light strongly interacts with structures that are of a similar scale to its wavelength, typically nanoscale features for light in the visible spectrum. However, the optical response of these nanostructures is usually fixed during the fabrication. Phase change materials offer a way to tune the properties of these structures in nanoseconds. Until now, phase change active photonics has used materials that strongly absorb visible light, which limits their application in the visible spectrum. In contrast, Sb2S3 is an underexplored phase change material with a bandgap that can be tuned in the visible spectrum from 2.0 to 1.7 eV. This tuneable bandgap is deliberately coupled to an optical resonator such that it responds dramatically in the visible spectrum to Sb2S3 reversible structural phase transitions. It is shown that this optical response can be triggered both optically and electrically. High‐speed reprogrammable Sb2S3 based photonic devices, such as those reported here, are likely to have wide applications in future intelligent photonic systems, holographic displays, and microspectrometers.